2012
DOI: 10.1088/1748-3182/7/3/036019
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish response to robotic fish: preference experiments on isolated individuals and small shoals

Abstract: Recently developed bioinspired robots imitate their live counterparts in both aspect and functionality. Nevertheless, whether these devices can be integrated within the ecological niche inspiring their design is seldom tested experimentally. An elemental research question concerns the feasibility of modulating spontaneous behaviour of animal systems through bioinspired robotics. The following study explores the possibility of engineering a robotic fish capable of influencing the behaviour of live zebrafish (Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
97
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 79 publications
12
97
2
2
Order By: Relevance
“…Experiments were filmed at 15 frames per second at a resolution of 800 × 600 pixels. A similar setup was used for other zebrafish-robot interactions experiments by our group [46][47][48][49][50][51]. Fish replicas, 3 cm in length, were fabricated using Acrylonitrile Butadiene Styrene (ABS) thermoplastic in a 3D prototyping machine (Dimension Elite, Stratasys Ltd., Eden Prairie, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were filmed at 15 frames per second at a resolution of 800 × 600 pixels. A similar setup was used for other zebrafish-robot interactions experiments by our group [46][47][48][49][50][51]. Fish replicas, 3 cm in length, were fabricated using Acrylonitrile Butadiene Styrene (ABS) thermoplastic in a 3D prototyping machine (Dimension Elite, Stratasys Ltd., Eden Prairie, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A servo motor at the top end of the attachment rod was oscillated about the vertical axis at 3 Hz. This local oscillation gave an appearance of undulating movement to the replica in addition to spatial coverage and was selected to match previous values of tail-beat frequency in studies with bioinspired robots [46,49,51]. Two such robotic arms were installed on either side of the tank to provide a uniform visual background to the live subject with respect to the two choices available on the sides of the tank.…”
Section: Methodsmentioning
confidence: 99%
“…Following earlier studies [9,13], the robot was rubberized and painted to resemble the colour and stripe pattern of zebrafish. Further details on the chromatic contrast of the robotic fish when compared with live subjects are presented in the electronic supplementary material.…”
Section: Robotic-fishmentioning
confidence: 99%
“…Differently from earlier studies [9,13], where the behaviour of zebrafish in response to a predetermined (open-loop) stimulus has been analysed, in this work, fish motion is acquired through an image-based tracking software to drive the tail-beating frequency of the robotic-fish in real-time (closed-loop). The tail section is composed of a compliant passive caudal fin and a rigid part actuated by a servomotor to undulate at a desired amplitude and angular speed.…”
Section: Introductionmentioning
confidence: 99%
“…Both have found that a small subset of the population, trained with pertinent knowledge, such as the location of a food source, is able to influence the swimming direction of the shoal [22,23]. Effects of controlled external stimuli have also been studied, specifically the use of biomimetic robots (ethorobotics) to elicit responses both at the individual level [24][25][26] and in the collective behaviour of fish shoals [27][28][29][30]. Meanwhile, purely computational studies have explored the dynamic response of biologically inspired mobile agents in the presence of an informed agent or group of agents [31][32][33].…”
Section: Introductionmentioning
confidence: 99%